Self‐hypnosis for intrapartum pain management in pregnant nulliparous women: a randomised controlled trial of clinical effectiveness. (11th May 2015) - Downe, S; Finlayson, K; Melvin, C; Spiby, H; Ali, S; Diggle, P; Gyte, G; Hinder, S; Miller, V; Slade, P; Trepel, D; Weeks, A; et al.
<x xml:space="preserve">Abstract</x> Objective (Primary) To establish the effect of antenatal group self‐hypnosis for nulliparous women on intra‐partum epidural use. Design Multi‐method randomised control trial (RCT). Setting Three NHS Trusts. Population Nulliparous women not planning elective caesarean, without medication for hypertension and without psychological illness. Methods Randomisation at 28–32 weeks' gestation to usual care, or to usual care plus brief self‐hypnosis training (two × 90‐minute groups at around 32 and 35 weeks' gestation; daily audio self‐hypnosis CD). Follow up at 2 and 6 weeks postnatal. Main outcome measures Primary: epidural analgesia. Secondary: associated clinical and psychological outcomes; cost analysis. Results Six hundred and eighty women were randomised. There was no statistically significant difference in epidural use: 27.9% (intervention), 30.3% (control), odds ratio (OR) 0.89 [95% confidence interval (CI): 0.64–1.24], or in 27 of 29 pre‐specified secondary clinical and psychological outcomes. Women in the intervention group had lower actual than anticipated levels of fear and anxiety between baseline and 2 weeks post natal (anxiety: mean difference −0.72, 95% CI −1.16 to −0.28, P = 0.001); fear (mean difference −0.62, 95% CI −1.08 to −0.16, P = 0.009) [Correction added on 7 July 2015, after first online publication: 'Mean difference' replaced 'Odds ratio (OR)' in the preceding sentence.]. Postnatal response rates were 67% overall at 2 weeks. The additional cost in the intervention arm per woman was £4.83 (CI −£257.93 to £267.59). Conclusions Allocation to two‐third‐trimester group self‐hypnosis training sessions did not significantly reduce intra‐partum epidural analgesia use or a range of other clinical and psychological variables. The impact of women's anxiety and fear about childbirth needs further investigation.